2017
DOI: 10.1177/0300060517734678
|View full text |Cite
|
Sign up to set email alerts
|

Effects of positive end-expiratory pressure on intraoperative core temperature in patients undergoing posterior spine surgery: prospective randomised trial

Abstract: ObjectivePositive end-expiratory pressure (PEEP) causes carotid baroreceptor unloading, which leads to thermoregulatory peripheral vasoconstriction. However, the effects of PEEP on intraoperative thermoregulation in the prone position remain unknown.MethodsThirty-seven patients undergoing spine surgery in the prone position were assigned at random to receive either 10 cmH2O PEEP (Group P) or no PEEP (Group Z). The primary endpoint was core temperature 180 minutes after intubation. Secondary endpoints were delt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…First of all, compared to the supine position, passive warming is harder to work in lateral position and lithotomy position with less contact area to the operation bed, less sheets or surgical draping and higher heat dissipation. Furthermore, lithotomy position is susceptible to hypothermia because baroreceptor loading augments perioperative hypothermia in anesthetised and paralysed subjects by reducing the body temperature threshold for peripheral vasoconstriction (Edgcombe et al, 2008; Seo et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…First of all, compared to the supine position, passive warming is harder to work in lateral position and lithotomy position with less contact area to the operation bed, less sheets or surgical draping and higher heat dissipation. Furthermore, lithotomy position is susceptible to hypothermia because baroreceptor loading augments perioperative hypothermia in anesthetised and paralysed subjects by reducing the body temperature threshold for peripheral vasoconstriction (Edgcombe et al, 2008; Seo et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Three trials investigated high (5–12 cm H 2 0) vs. low PEEP (0–4 cm H 2 0), one including recruitment maneuvers 45–47 . Bluth et al included 989 patients; the two other trials included ≤150 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Three trials investigated high (5-12 cm H 2 0) vs. low PEEP (0-4 cm H 2 0), one including recruitment maneuvers. [45][46][47] None of the six trials found a difference in postoperative pain.…”
Section: Tidal Volume and Positive End-expiratory Pressurementioning
confidence: 99%
“…Apart from applying active heating methods in patients, the effectiveness of anesthesia in preventing hypothermia is a research topic [17, 18]. In a study comparing lung-protective ventilation and conventional high tidal volume ventilation, lung-protective ventilation did not have an advantage in maintaining the patient’s core temperature [19].…”
Section: Discussionmentioning
confidence: 99%